1998
DOI: 10.1159/000007516
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide in the Treatment of Collagenous Colitis

Abstract: Collagenous colitis is characterized by watery diarrhea and inflammatory infiltration associated with a subepithelial collagen deposit on colonic biopsies despite a normal or subnormal endoscopic appearance. We here describe 5 patients treated with the locally active steroid budesonide. Complete and partial response was observed in 3 and 2 patients, respectively. Budesonide thus seems to be of therapeutic benefit in collagenous colitis. Prospective randomized long-term studies are needed to support this hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 5 publications
1
6
1
Order By: Relevance
“…This is in accordance with previous open studies 8 9 and a recently published placebo controlled trial. 10 Collagenous colitis is characterised by watery diarrhoea and in the present study up to 10 bowel movements a day were found.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous open studies 8 9 and a recently published placebo controlled trial. 10 Collagenous colitis is characterised by watery diarrhoea and in the present study up to 10 bowel movements a day were found.…”
Section: Discussionsupporting
confidence: 93%
“…In many cases, even colonoscopy does not detect any signs of inflammation; therefore, in patients with chronic watery diarrhea, biopsy of even apparently normal mucosa is mandatory. 5,10,14 The findings of Cammarota et al 9 on endoscopic sonography are somewhat different from the findings in our case. First, the predominant finding of watery stool in the large bowel could not be detected on endoscopic sonography because of preparatory bowel cleansing.…”
Section: Discussioncontrasting
confidence: 92%
“…It is characterized by watery diarrhea associated with inflammatory infiltration and subepithelial collagen deposits on colonic biopsies despite a normal or subnormal endoscopic appearance. 10 One suggested pathophysiologic mechanism for diarrhea in collagenous colitis is a reduced permeability of electrolytes and water in the colonic mucosa. 11 Sonography is a very sensitive method for detecting fluid within the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, budesonide is universally employed to treat asthma, and asthma was recently associated with reduced risk of developing pancreatic ductal adenocarcinoma (30). Furthermore, budesonide is also used to treat the collagenous colitis, a rare inflammatory disorder associated with collagen accumulation in the colorectal mucosa (31,32), and its therapeutic efficacy is ascribed to the anti-inflammatory activity of GCs (33). Thus, our unexpected findings that budesonide blocks mesenchymal transition interfering with collagen accumulation provide novel insights into its therapeutic effects.…”
Section: Discussionmentioning
confidence: 87%